Volumes de recipientes no crescimento de espécies florestais nativas - Dias, Tânia Fontana (2011)
In order to provide information regarding the production of seedlings of forest species of Atlantic Forest, important segment of forest restoration, the study evaluated the growth of seedlings, Calophillum brasiliense (guanandi), Cariniana estrellensis (jequitibá white), Peltophorum dubium (angico canjiquinha) e Schinus terebinthifolius (red pepper tree) grown in containers of different dimensions. The study was conducted in the nursery trade Agroforestry Atlantic (AMA), city of Teixeira de Freitas, Bahia, located at 17 ° 31'08 "south latitude and 39 º 44'30" west longitude. The statistical design was randomized blocks, with four replications and five treatments composed of tubes volumetric capacity of 53, 115, 180 and 280 cm³ and plastic bag of 560 cm³. Each species was an experiment independent of the others. The influence of the volume of the vessel growth and quality of the seedlings was determined by the following biometric parameters: shoot height, collar diameter, shoot dry biomass, root and total leaf area, high levels of relations and diameter, dry biomass and root and Quality of Dickson. To carry out the assessments were taken at random 15 central plants in each plot. The non-destructive evaluations began 30 days after transplantation for recipients, and repeated monthly until the seedlings showed morphological suitable for planting. During this time the experiment was completed, performing destructive evaluations. The results were subjected to analysis of variance SAEG statistical package (Statistical Analysis System), and the treatment means compared by Tukey test at 5% probability. The volume of container has significantly influenced the development of the plants for some species, indicating that plant growth was limited by restricting the root system. For Calophillum xi brasiliense (guanandi), there was statistical similarity between the seedlings of the tubes 180, 280 cm³ and 560 cm³ bag for all parameters evaluated. For species Cariniana estrellensis (jequitibá white), the average cartridge of 280 cm³ and 560 cm³ bag, were statistically similar for some parameters. Seedlings Peltophorum dubium (yopo canjiquinha), produced in the bag 560cm³ had higher averages for all parameters, and the tubes 180 and 280cm³ form similar in most parameters. To Schinus terebinthifolius (red pepper tree), the highest averages for all parameters, correspond to bag 560 cm³, except for the index that Dickson was similar between the tubes 180 and 280 cm³ and 560 cm³ bag. Even the highest average of indicators of quality of forest seedlings match the bag 560 cm³, its use may be impaired, since it produced all species showed folding of the root system and longer for aggregation of the root ball to the substrate. Considering substrate consumption, space requirements, length of stay in the nursery, labor, greater care with irrigation and monitoring of pests and diseases, depending on the species, may be more feasible using vessels of 180 or 280 cm³.